Metabolic adaptation to a disruption in oxygen supply during myocardial ischemia and reperfusion is underpinned by temporal and quantitative changes in the cardiac proteome - Lee, Chuen Neng (2013)
Despite decades of intensive research, there is still no effective treatment for ischemia/reperfusion (I/R) injury, an important corollary in the treatment of ischemic disease. I/R injury is initiated when the altered biochemistry of cells after ischemia is no longer compatible with oxygenated microenvironment (or reperfusion). To better understand the molecular basis of this alteration and subsequent incompatibility, we assessed the temporal and quantitative alterations in the cardiac proteome of a mouse cardiac I/R model by an iTRAQ approach at 30 min of ischemia, and at 60 or 120 min reperfusion after the ischemia using sham-operated mouse heart as the baseline control. Of the 509 quantified proteins identified, 121 proteins exhibited significant changes (p-value < 0.05) over time and were mostly clustered in eight functional groups: Fatty acid oxidation, Glycolysis, TCA cycle, ETC (electron transport chain), Redox Homeostasis, Glutathione S-transferase, Apoptosis related, and Heat Shock proteins. The first four groups are intimately involved in ATP production and the last four groups are known to be important in cellular antioxidant activity. During ischemia and reperfusion, the short supply of oxygen precipitates a pivotal metabolic switch from aerobic metabolism involving fatty acid oxidation, TCA, and phosphorylation to anaerobic metabolism for ATP production and this, in turn, increases reactive oxygen species (ROS) formation. Therefore the implication of these 8 functional groups suggested that ischemia-reperfusion injury is underpinned in part by proteomic alterations. Reversion of these alterations to preischemia levels took at least 60 min, suggesting a refractory period in which the ischemic cells cannot adjust to the presence of oxygen. Therefore, therapeutics that could compensate for these proteomic alterations during this interim refractory period could alleviate ischemia-reperfusion injury to enhance cellular recovery from an ischemic to a normoxic microenvironment. Among the perturbed proteins, Park7 and Ppia were selected for further investigation of their functions under hypoxia. The results show that Park7 plays a key role in regulating antioxidative stress and cell survival, and Ppia may function in coping with the unfolded protein stress in the I/R condition.